Gender Differences in the Text Messaging of Young Jordanian University Students: An Analysis of Linguistic Feature - Al Rousan, Rafat Mahmoud (2013)
In spite of being extensively studied in face-to-face communication, gender differences remain widely unexplored within text messaging. The objectives of this study are to explore gender differences in the use of linguistic features in the text messaging of young Jordanian male and female university students with regard to (1) lexical features (abbreviations, acronyms, shortenings, borrowing, derivation, blending, compounding, and conversion), (2) syntactic features (deletion of subject pronoun, deletion of subject pronoun and auxiliary, deletion of copular/ modal verb, and deletion of article), and (3) typographical features (punctuation, letter and number homophones, phonetic spellings, onomatopoeic words, and emoticons). Theoretically, the study is guided by Bodomo and Lee‟s model of Technology-conditioned Language Change and Use and Herring‟s approach of Computer-Mediated Discourse Analysis. Three techniques of qualitative data collection were used: open-ended questionnaires, user diaries and semi-structured interviews to elicit information on the features reflected in the text messages of the students. One hundred students responded to a questionnaire while twenty students participated in semi-structured interviews. The sixty students who participated in the user diaries provided a corpus of 1,612 text messages which were analyzed according to the gender of the senders. The messages were also analyzed for occurrences of lexical, syntactic, and typographical features, and compared for differences across gender. Lexical features were categorized based on Yule‟s (2009) categorization of word-formation processes while syntactic and typographical features were categorized according to Hård af Segrestad‟s (2002) and Thurlow's (2003) typology of linguistic features of text messaging. The findings of this study reveal the existence of gender differences in the text messages of the Jordanian students in all the three linguistic features. The females tend to use more lexical features than males, whereas the males tend to favor the deletion of syntactic features more than females. In terms of typographical features, the males tend to use more letter and number homophones and phonetic spelling than females while the females tend to use more punctuation, onomatopoeic words and emoticons than males. The findings corroborate with previous findings on differences across gender in text messaging as well as in face-to-face and computer-mediated communication. This study contributes to the literature related to the study of language in terms of the use of some of the linguistic features and their variations in text messaging between males and females. Some implications and recommendations are provided in this study.